2016
DOI: 10.1111/mmi.13426
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of a mechanism of oxidative stress regulation in Francisella tularensis live vaccine strain

Abstract: Summary Francisella tularensis causes a lethal human disease known as tularemia. As an intracellular pathogen, Francisella survives and replicates in phagocytic cells, such as macrophages. However, to establish an intracellular niche, Francisella must overcome the oxidative stress posed by the reactive oxygen species (ROS) produced by the infected macrophages. OxyR and SoxR/S are two well-characterized transcriptional regulators of oxidative stress responses in several bacterial pathogens. Only the OxyR homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 73 publications
(87 reference statements)
4
36
1
Order By: Relevance
“…Overall, it appears that OxyR, as expected, regulates katG in the LVS strain, however, the regulation does not completely abolish its expression as is the case observed for various other bacterial species, e.g., E. coli (Michán et al, 1999), Salmonella enterica (Morgan et al, 1986), Haemophilus influenza (Whitby et al, 2012), or Moraxella catarrhalis (Hoopman et al, 2011). In both the present study, and in the previous study, it was observed that the lack of OxyR led to marked suppression of ahpC2 (Ma et al, 2016). In addition Ma et al demonstrated suppressed expression of both katG and sodB in Δ oxyR by real-time PCR and demonstrated that OxyR binds to the upstream promoter regions of each gene.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Overall, it appears that OxyR, as expected, regulates katG in the LVS strain, however, the regulation does not completely abolish its expression as is the case observed for various other bacterial species, e.g., E. coli (Michán et al, 1999), Salmonella enterica (Morgan et al, 1986), Haemophilus influenza (Whitby et al, 2012), or Moraxella catarrhalis (Hoopman et al, 2011). In both the present study, and in the previous study, it was observed that the lack of OxyR led to marked suppression of ahpC2 (Ma et al, 2016). In addition Ma et al demonstrated suppressed expression of both katG and sodB in Δ oxyR by real-time PCR and demonstrated that OxyR binds to the upstream promoter regions of each gene.…”
Section: Discussionsupporting
confidence: 82%
“…A similar investigation has been performed recently by Ma et al which studied the role of OxyR in LVS (Ma et al, 2016). It was found that OxyR controlled transcription of katG and the findings agree with the reduced catalase activity of Δ oxyR observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations